Annulment of Oil Licences in Nigeria's Upstream Petroleum Sector: A Legal Critique of the Costs and Benefits - Olujobi, Olusola Joshua; Oyewunmi, Olabode Adeleke (International Journal of Energy Economics and Policy, 2017)
Owing to various reasons, tenable and untenable, successive governments in Nigeria have annulled licenses duly granted to identifiable upstream petroleum operators. With due sense of circumspect, when irregularities manifest in the process and the grant of substantive licences, such does not vest in the government an unfettered right to annul the licence. There are evidences of such occurrence inspite of established procedures regulating annulments, commonly referred to as revocation or cancellation. This paper is a critique of the annulment of oil licenses and the associated contractual-regulatory dimensions. The validity of the Federal Government's actions also comes to the fore, particularly in the light of renewed drive to attract investments into the upstream sector. Thus, as some benefits are accruable to the players, it is also important to appraise the consequential costs attributable to undue annulment of oil licenses. The paper adopts a descriptive analytical method of available facts, expounds requisite statutory provisions and utilizes judicial precedents to highlight the context of the study. It is imperative that the Federal Government adheres to established procedures on oil license annulment, as a contrary posture will amount to several negative outcomes. Keywords: Oil, Upstream, Nigeria, Licence, Annulment, Contracts, Regulations JEL Classifications: K32, K12, K2, K42, P28